PENGARUH DEBT TO EQUITY RATIO DAN CURRENT RATIO TERHADAP HARGA SAHAM PADA PT WIJAYA KARYA (PERSERO) Tbk PERIODE 2013-2023 - Gina Maya Putri, Fadillah; Watiningsih, Ferdina (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Debt To Equity Ratio partially on stock prices and Current Ratio partially on stock prices and to determine the simultaneous influence of Debt To Equity Ratio and Current Ratio on stock prices in PT Wijaya Karya (persero) Tbk for the 2013-2023 period. The selected population is the financial statements of PT Wijaya Karya (persero) Tbk, with the samples used being balance sheets, income statements, notes on financial statements and stock overviews for the 2013-2023 period. This study uses a quantitative approach. The analysis methods used are descriptive test, classical assumption test, multiple linear regression, hypothesis test and determination coefficient. Based on the results of the study using the Debt To Equity Ratio t-test, it has a negative and significant effect on the stock price with a significance value of 0.030 < 0.05 and a calculated value of -2.626 > a ttable of 2.306. The Current Ratio has no significant effect on the stock price with a significance value of -1.094 > 2.306. The results of the simultaneous test (Test F) show that the Debt To Equity Ratio and Current Ratio have an effect on the stock price with a significance value of 0.043 < 0.05 and a value of Fcal 4.809 > Ftable 4.07. And based on the coefficient of determination, it can be said that the influence of the Debt To Equity Ratio and Current Ratio on the Stock Price is 43.2%, while the rest is 56.8% influenced by other variables that were not studied in this study.